2009
DOI: 10.1111/j.1365-277x.2009.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation to determine the nutritional adequacy and individuals experience of a very low fat diet used to treat type V hypertriglyceridaemia

Abstract: Compliance could be improved through extensive education on labelling, eating during special occasions such as Christmas, birthdays and eating out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…However, using a telephone to conduct interviews was necessary as participants were recruited across a wide geographical area (metropolitan and non-metropolitan regions of Victoria, Australia). Telephone interviewing is a beneficial mode of collecting qualitative data as the views of participants in more remote regions can be included [ 58 , 66 , 67 ]. Also, one-on-one interviews may provide greater depth than possible in other forms of qualitative research such as focus groups, as concentrated time is spent with each participant [ 65 ], and participants may be more relaxed and willing to talk freely [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, using a telephone to conduct interviews was necessary as participants were recruited across a wide geographical area (metropolitan and non-metropolitan regions of Victoria, Australia). Telephone interviewing is a beneficial mode of collecting qualitative data as the views of participants in more remote regions can be included [ 58 , 66 , 67 ]. Also, one-on-one interviews may provide greater depth than possible in other forms of qualitative research such as focus groups, as concentrated time is spent with each participant [ 65 ], and participants may be more relaxed and willing to talk freely [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased food preparation time and financial burden, as well as an increased level of knowledge and cooking skills must be considered . Studies have found that barriers to following a restricted diet include increased burden, lack of available food, and lack of flavour and variety . Whilst these constraints may not concern some individuals who choose to follow these diets, the literature suggests adherence to low‐carbohydrate diets is challenging .…”
Section: Low‐carbohydrate Dietsmentioning
confidence: 99%
“…Mothers make daily decisions related to planning meals, shopping for food and preparing meals 6 . Several authors have commented on the burden this places on women, 2,5 and a few have studied the extra burden imposed by catering to a child with special dietary need 11,12 . Given the burden imposed by a special diet, these diets should be based on evidence.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several authors have commented on the burden this places on women, 2,5 and a few have studied the extra burden imposed by catering to a child with special dietary need. 11,12 Given the burden imposed by a special diet, these diets should be based on evidence. The best test of effectiveness is a randomised trial.…”
Section: Introductionmentioning
confidence: 99%